2013
DOI: 10.1371/journal.pone.0054261
|View full text |Cite
|
Sign up to set email alerts
|

Cyclic AMP Enhances TGFβ Responses of Breast Cancer Cells by Upregulating TGFβ Receptor I Expression

Abstract: Cellular functions are regulated by complex networks of many different signaling pathways. The TGFβ and cAMP pathways are of particular importance in tumor progression. We analyzed the cross-talk between these pathways in breast cancer cells in 2D and 3D cultures. We found that cAMP potentiated TGFβ-dependent gene expression by enhancing Smad3 phosphorylation. Higher levels of total Smad3, as observed in 3D-cultured cells, blocked this effect. Two Smad3 regulating proteins, YAP (Yes-associated protein) and TβR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 63 publications
0
28
0
Order By: Relevance
“…A recent study suggested that cAMP can promote TGF-β/-Smad3-mediated expression in breast cancer cells by upregulating the expression of the TGF-β receptor TβRI, and a 3 h or 6 h duration of forskolin treatment is sufficient to significantly raise TβRI expression indicating that TβRI levels rose early in response to forskolin [16]. These imply that in MDCK cells, forskolin-promoted TGF-β/ Smad2-mediated expression may also by regulating TβRI expression.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study suggested that cAMP can promote TGF-β/-Smad3-mediated expression in breast cancer cells by upregulating the expression of the TGF-β receptor TβRI, and a 3 h or 6 h duration of forskolin treatment is sufficient to significantly raise TβRI expression indicating that TβRI levels rose early in response to forskolin [16]. These imply that in MDCK cells, forskolin-promoted TGF-β/ Smad2-mediated expression may also by regulating TβRI expression.…”
Section: Discussionmentioning
confidence: 99%
“…One study suggested that cAMP can promote TGF-β/-Smad3-mediated expression in breast cancer cells by up-regulating the expression of the TGF-β receptor TβRI [16]. Another study found that cAMP-PKA can inhibit the enhancement of collagen type I mRNA expression caused by TGF-β, which was reversed by pre-treatment with H89 in human peritoneal mesothelial cells (HPMC) [17].…”
Section: Introductionmentioning
confidence: 99%
“…RNA isolation, cDNA synthesis and quantitative (Q) PCR were performed as described [48]. The RNA isolation kit was purchased from Roche and the dNTP mix was from Qiagen.…”
Section: Methodsmentioning
confidence: 99%
“…Protein extractions and Western blot analysis were carried out as described [48]. Briefly, adherent cells were scraped off, pelleted and resuspended in 400 μl buffer A (10 mM HEPES (pH 7.9), 10 mM KCl, 0.1 mM EDTA, 0.1 mM EGTA).…”
Section: Methodsmentioning
confidence: 99%
“…Several subsequent studies, using scaffold‐based technologies for 3D models assembly provide evidence that BM‐MSCs exert a positive effect in cancer cell survival and migratory capacity. In fact, cells co‐cultured in tissue mimetic scaffolds including those based on: i) collagen hydrogels; ii) silk‐fibroin scaffolds; or iii) porous chitosan scaffolds containing hydroxyapatite organotypic as bone mimetics laden with undifferentiated or differentiated MSCs, evidence their capability to up‐regulate the expression of EMT‐related genes in cancer cells, to induce higher migratory capacity (Figure ), and to enhance proliferation through different signaling factors.…”
Section: Cancer‐mscs Co‐culture Relevance In 3d In Vitro Tumor Modelsmentioning
confidence: 99%